A Systematic Review of Organizational Ambidexterity and Public Value in Local Government - NDLOVU N.; OCHARA N.M.; MARTIN R.L. (Communications of International Proceedings, 2021)
Despite the push for digital innovation, a matter that promotes public value, through efficient electronic dissemination of information, events from developing countries seem to indicate that, public value still remain a scenario which is yet to become a reality, particularly in local government. This paper provides a systematic review of the literature on the effects of organizational ambidexterity on public value, with a particular focus on exploitative and explorative innovation. The extant literature was identified through Google scholar, Emerald Insight and Science Direct database, from 2010 to 2020. Only academic articles with relevant discussion encompassing the two constructs were reviewed. The findings of this review indicate that several studies have been conducted in the area of organizational ambidexterity. These studies predominantly focused in the private sector, and as such, there is a paucity of studies that focused on organizational ambidexterity in the context of local government particularly from the developing countries. Based on the findings, a conceptual framework is proposed, which presents two constructs namely; exploitative innovation and explorative innovation that are used to measure organizational ambidexterity for the creation of public value.
Keywords: Ambidexterity; Public Value; Exploitative Innovation; Explorative Innovation.